Interference Screw versus Cement Fixation in Anterior Cruciate Ligament Soft Tissue Grafts: A Biomechanical Study - Patel, Jay; Kadkoy, Yazan; Helbig, Thomas; Rupani, Mohammed; Cuppari, Nicholas; Cortes, Ricardo; Wetterstrand, Charlene; Lu, Michael T.; Paglia, David N.; Galdi, Balazs; Beiro, Cristobal (The Journal of Knee Surgery, 2023)
Shortcomings of fixation have been reported as a source of graft failure in anterior cruciate ligament (ACL) reconstruction. While interference screws have long been used as fixation devices for ACL reconstruction, they are not without complications. Previous studies have highlighted the use of bone void filler as a fixation method; however, no biomechanical comparisons using soft tissue grafts with interference screws exist to our knowledge. The purpose of this study is to evaluate the fixation strength of a calcium phosphate cement bone void filler compared with screw fixation in an ACL reconstruction bone replica model with human soft tissue grafts. In total, 10 ACL grafts were constructed using semitendinosus and gracilis tendons harvested from 10 donors. Grafts were affixed with either an 8–10 mm × 23 mm polyether ether ketone interference screw (n = 5) or with approximately 8 mL of calcium phosphate cement (n = 5) into open cell polyurethane blocks. Graft constructs were tested to failure in cyclic loading under displacement control at a rate of 1 mm per second. When compared with screw construct, the cement construct showed a 978% higher load at yield, 228% higher load at failure, 181% higher displacement at yield, 233% higher work at failure, and a 545% higher stiffness. Normalized data for the screw constructs relative to the cement constructs from the same donor showed 14 ± 11% load at yield, 54 ± 38% load at failure, and 172 ± 14% graft elongation. The results of this study indicate that cement fixation of ACL grafts may result in a stronger construct compared with the current standard of fixation with interference screws. This method could potentially reduce the incidence of complications associated with interface screw placement such as bone tunnel widening, screw migration, and screw breakage.
Keywords: graft fixation; biomechanics; ACL reconstruction